(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Every nation on the planet suffers from subpar or fake medications, which can be fatal, cause manufacturers to lose money, and cause consumers to lose faith in the medical system. This enumerative review’s objective was to examine the amount of subpar medications, their effects on the general public’s health, and the preventative steps the Indian pharmaceutical regulatory system had made. Studies, books, and news from both the public and private sectors were gathered from reputable publications and websites. All information from 2000 to 2013 was gathered, analysed, and synthesised to tell the true tale of India’s subpar medicine supply. More stricter regulation and judicial action against the issue are urgently needed to reduce spurious/falsely labelled/falsified/counterfeit/drugs, or pharmaceuticals of substandard quality. To protect and advance the general public’s health, India has still implemented some preventative measures throughout the nation.